Random stability and hyperstability of multi quadratic mappings - Park, Choonkil; Bodaghi, Abasalt; Alias, Idham Arif (Element D.O.O., 2022)
In this paper, we introduce a new quadratic functional equation. In light of this equation, we define the multi-quadratic mappings and reduce the system of n equations defining the multi-quadratic mappings to a single equation. We also obtain some stability and hyperstability results concerning multi-quadratic mappings in the setting of random normed spaces.